Transmitted drug resistance mutations and trends of HIV-1 subtypes in treatment-naïve patients: A single-centre experience. (March 2020) - Mazzuti, Laura; Melengu, Taulant; Falasca, Francesca; Calabretto, Marianna; Cella, Eleonora; Ciccozzi, Massimo; Mezzaroma, Ivano; Iaiani, Giancarlo; Spaziante, Martina; d'Ettorre, Gabriella; Fimiani, Caterina; Vullo, Vincenzo; et al.
Highlights: Primary drug resistance can reduce the efficacy of antiretroviral therapy. HIV-1 non-B subtypes are increasing in Italy. The frequency of transmitted drug resistance mutations remains stable over the years. Major mutation to Integrase inhibitors in naive patients was found for the first time in Italy. Abstract: Objectives: Transmitted drug resistance (TDR) and HIV-1 genetic diversity may affect treatment efficacy and clinical outcomes. Here we describe the circulating viral subtypes and estimate the prevalence of drug resistance among antiretroviral therapy (ART)-naïve patients attending Sapienza University Hospital (Rome, Italy) from 2006–2017. Methods: Genotypic resistance testing (GRT) was performed on 668 ART-naïve patients for integrase ( n = 52), protease and reverse transcriptase ( n = 668) sequences. Results: Twenty-one different HIV-1 subtypes and circulating recombinant forms (CRFs) were identified. Subtype B was the most common (67.1%), followed by CRF02_AG (8.4%), and subtypes C and F (both 6.0%). A significantly increase in the proportion of non-B strains ( P < 0.001) and the rate of non-Italian patients was observed over time. The overall prevalence of TDR was 9.4% (NRTI, 4.2%; NNRTI, 5.8%; and PI, 1.0%) and was higher in subtype B strains. Transmitted INSTI mutations (Q148H and G140S) responsible for high-level resistance to raltegravir and elvitegravir and intermediate resistance to dolutegravir and bictegravir were found, for the first time, in two individuals. Minor or accessory INSTI mutations were detected in 17.3% of patients. No significant decrease in the prevalence of TDR was documented over time. Conclusion: The significant increase in non-B subtypes suggests that the molecular epidemiology of HIV-1 is changing. Detection of a major INSTI mutation in two ART-naïve patients highlights the importance of performing GRT before commencing treatment. This finding and the lack of a significant reduction in TDRs underline the importance of continuous surveillance of resistance mutations.